2016
DOI: 10.3139/146.111384
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical properties of single-walled and multi-walled carbon nanotube polycarbonate polyurethane composites with a focus on self-healing

Abstract: Single walled and multi walled carbon nanotubes were incorporated into a high molar mass polycarbonate polyurethane via ultrasonication. The polycarbonate polyurethane which is free of any healing additives has the capacity to partially re-heal after rupture. The formation of the polyurethane/carbon nanotube composites has been shown to greatly improve the self-healing characteristics. Moreover, there is an increase in the thermal and mechanical properties of the thermoplastic composites. Herein we investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…MWCNTs with rolled graphitic layers with remarkable mechanical 1719 , thermal 20,21 and electrical 2224 properties can be applied as reinforcement of fiber/matrix composites to achieve improved properties. In the last decades, the use of MWCNTs as filler in thermoplastics such as PE 2527 , PP 2831 or polycarbonate 3234 has been widely studied. However, to take advantages of the reinforcement characteristics of MWCNTs, hindering factors have to be eliminated, such as the strong Van der Waals interaction between the MWCNTs and their poor surface wetting properties.…”
Section: Introductionmentioning
confidence: 99%
“…MWCNTs with rolled graphitic layers with remarkable mechanical 1719 , thermal 20,21 and electrical 2224 properties can be applied as reinforcement of fiber/matrix composites to achieve improved properties. In the last decades, the use of MWCNTs as filler in thermoplastics such as PE 2527 , PP 2831 or polycarbonate 3234 has been widely studied. However, to take advantages of the reinforcement characteristics of MWCNTs, hindering factors have to be eliminated, such as the strong Van der Waals interaction between the MWCNTs and their poor surface wetting properties.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research on the novel PCPU has shown that our polymer is ultrasoft with a shore A hardness of 70, has high tensile strength and shows partial self‐healing, which can be enhanced with the addition of carbon nanotubes . We are now looking at the effect of transforming the PCPU to fiber membranes to investigate whether the thermal and mechanical properties are affected.…”
Section: Introductionmentioning
confidence: 96%
“…PCPU is a thermoplastic PU (TPU), which is a class of polymers that possess excellent properties, including toughness, abrasion resistive, excellent hydrolytic stability, elastomeric, and durability, making it versatile for widespread uses . Because of its biocompatibility, non‐toxicity, robustness, and functionality, TPUs can be used in the biomedical industry as implantable devices (vascular grafts, pacemaker leads, blood bags, bladders, and artificial heart valves) and medical applications .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation